Neoadjuvant Chemotherapy Followed by Surgery Versus Abdominal Radical Hysterectomy Alone for Oncological Outcomes of Stage IB3 Cervical Cancer—A Propensity Score Matching Analysis - Li, Weili; Zhang, Wenling; Sun, Lixin; Wang, Li; Cui, Zhumei; Zhao, Hongwei; Wang, Danbo; Zhang, Yi; Guo, Jianxin; Yang, Ying; Wang, Wuliang; Bin, Xiaonong; et al. (Frontiers in Oncology, 2021)
Objective: To compare the 5-year overall survival (OS) and disease-free survival (DFS) of patients who received neoadjuvant chemotherapy followed by surgery (NACT) and abdominal radical hysterectomy alone (ARH) for cervical cancer. Methods: We retrospectively compared the oncological outcomes of 1410 patients with stage IB3 cervical cancer who received NACT (n=583) or ARH (n=827). The patients in the NACT group were divided into a NACT-sensitive group and a NACT-insensitive group according to their response to chemotherapy. Results: The 5-year oncological outcomes were significantly better in the NACT group than in the ARH group (OS 96.2% vs 91.2%, p=0.002; DFS 92.2% vs 87.5%, p=0.016). Cox multivariate analysis suggested that NACT was independently associated with better 5-year OS (HR=0.521; 95% CI, 0.304-0.892; p=0.025), but it was not an independent factor for 5-year DFS (HR=0.752; 95% CI, 0.508-1.114; p=0.155). After matching, the 5-year oncological outcomes of the NACT group were better than those of the ARH group. Cox multivariate analysis suggested that NACT was still an independent protective factor for 5-year OS (HR=0.503; 95% CI, 0.275-0.918; p=0.025). The proportion of patients in the NACT group who received postoperative radiotherapy was significantly lower than the proportion in the ARH group (p<0.001). Compared to the ARH group, the NACT-sensitive group had similar results as the NACT group. The NACT-insensitive group and the ARH group had similar 5-year oncological outcomes and proportions of patients receiving postoperative radiotherapy. Conclusion: Among patients with stage IB3 cervical cancer, NACT improved 5-year OS and was associated with a reduction in the proportion of patients receiving postoperative radiotherapy. These findings suggest that patients with stage IB3 cervical cancer, especially patients who are sensitive to chemotherapy, should choose NACT followed by surgery.